Improving Student’s Independence and Learning Outcomes Through Website-based Instructional Media - Madziatul Churiyah; Andi Basuki; Raisa Fitri; Vina Nur Machabbatulillah; Yashinta Ula Qomarina (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2021)
The use of digital learning is a critical component of developing technology information and communication skills. The purpose of this study aims to develop a web-based Petty Cash Management Information System for financial administration courses to increase student autonomy and learning outcomes. This type of research and development employed a modified version of Borg and Gall’s Research and Development model. The study’s subjects included media and material experts serving as expert validators, six students serving as user validators, and large group test subjects. Quantitative data were gathered through the calculation of scores on validation questionnaires, independence questionnaires, and psychomotor test scores; qualitative data were gathered through interviews, criticisms, and suggestions. The independent sample t-test and descriptive qualitative analysis are used to analyze the data. The validation and trial results indicate that the learning media is appropriate for its designation, learning objectives, and ease of use and that it can be applied to support learning and improve student learning outcomes. The resulting product is unique in that it supports automation, complies with requirements, and features a distinct user interface for lecturers and students. Keywords: Financial Administration, Instructional Media, Learning Independence